The Interwar Gold Standard in Light of the Present. (11th April 2014) - Bholat, David
<x xml:space="preserve">Abstract</x> This symposium item belongs to a section headed: SYMPOSIUM: THE GREAT DEPRESSION AND THE EUROZONE CRISIS: LEARNING FROM THE PAST, which also includes What Does the 1930s' Experience Tell Us about the Future of the Eurozone? by Nicholas Crafts (DOI: 10.1111/jcms.12145), Gold Standard Lessons for the Eurozone? by Matthias Morys (DOI: 10.1111/jcms.12146), Policy Options for the Euro: Heterodoxy Ahead? by Scott Urban (DOI: 10.1111/jcms.12147).